Prośrodowiskowe kształtowanie terenów zieleni - propozycje dla dzielnicy Ursynów m.st. Warszawy - Justyna Staroszczyk; Antoni Skowroński (Studia Ecologiae et Bioethicae)
It is well known that green areas are a significant component of urban environment. Plants influence urban conditions in many ways; they have a positive effect on both people’s health and environmental issues, there are many reasons why the proportion of green areas in cities should be increased. It is important to take advantage of plant properties and suitable methods of shaping green areas to benefit nature.